Teaching management: a view from organizational theories and pedagogy - Ávila Guerrero, Flor Marlen (Universidad Pedagógica y Tecnológica de Colombia, 2010)
Therefore in this document is intended to travel through the conceptualization of government from the organizational and pedagogical and therefore is presented in four parts: the first relates to a review of the concept of administration, how addresses the administrative and organizational theories, the second gives an account of the pedagogy of teaching management in the third presents a discussion on the literature review conducted, which reveals a number of concerns that provide elements for the formulation research projects and finally show some points of arrival as opening the way to new perspectives and approaches on the subject.